EFFECT OF FREQUENCE AND PERIODS FEEDING OF CROSSBRED NATIVE CHICKEN ON METABOLISM ENERGY UTILIZATION EFICINCY - A., SETIAWAN; SUPRIJATNA, E.; MAHFUDZ, L.D. (Fakultas Peternakan Universitas Udayana, 2017)
This study was aimed to determine the appropriate feeding frequnce and feeding periods on crossbred nativechicken for better efficiency in metbolisme energi utilization. Thestudy used 252 one day oldunsex crossbred nativechickens with the average of initial body weight was 37.88 ± 1.89 g (CV = 5.02%) as materi. Comercial feed usedin this study. Experiment used Split Plot Design with 3 levels of feeding frequency as main plot F1 (once), F2(2times), F3(3 times) and 3 levels of feeding times periode as sub plot (P1start at 04:00 AM) P2 = start at 06:00 AM,P3 = start at 08:00 AM) with 4 replications that were arrange 36 experimental units, each unit wasconsisted of 7chickens. Data were analyzed using analysis of variance and F-test at 5% level. The results showed that there wasno effect (P>0,05)of interaction between feeding frequence and feeding periods or each factor on crossbred nativechicken efficiency in metabilisme energi utilization, so that combination of F1P3 (once feeding frequence with 14hours of feeding periods a day) most efficience for aplicates.